Contribution of antibody-mediated effector functions to the mechanism of efficacy of vaccines for opioid use disorders. - Kelcher, April M. Huseby (J Immunol, 2021)
Vaccines and monoclonal antibodies (mAb) offer promising strategies to treat substance use disorders (SUD) and prevent overdose. Despite vaccines and mAb against SUD demonstrating proof of efficacy, selectivity, and safety in animal models, it is unknown whether the mechanism of action of these immunotherapeutics relies exclusively on formation of antibody:drug complexes, or also involves antibody-mediated effector functions. Hence, this study tested whether the efficacy of active and passive immunization against drugs of abuse requires phagocytosis, intact Fc portion of the anti-drug antibody, Fcγ receptors (FcγR), or the neonatal Fc receptor (FcRn). The efficacy of a lead vaccine against oxycodone was not diminished in mice after depletion of macrophages or granulocytes. Anti-oxycodone F(ab’)(2) fragments resulted in lower serum level of F(ab’)(2) compared to intact mAb, and F(ab’)(2) were not as effective as the parent mAb in reducing distribution of oxycodone to the brain. Efficacy of vaccine and mAb against oxycodone was preserved in either FcγIII or FcγI-IV ablated (−/−) mice, suggesting FcγR are not required for antibody efficacy. Finally, both active and passive immunization against oxycodone in FcRn(−/−) mice yielded reduced efficacy compared to wild-type control mice. These data identified a role for FcRn, but not for phagocytosis or Fc-dependent effector functions, in mediating efficacy of vaccines and mAb against SUD. This study supports rational design of vaccines and mAb engineered for maximal neutralization activity and optimal FcRn binding.